(untitled) (Revista Internacional de Folkcomunicação, 2024)
This investigation seeks to understand the use of new information and communication technologies in the formation and maintenance of a cultural identity. The chatbot Estimada, accessed via WhatsApp and created to promote the culture of Florianópolis, aims to provide references that can "keep alive and accessible numerous relevant pieces of information about the city’s culture." The reflection on the attributes and responsibilities of the cultural bot conceptually draws from Cultural Studies and literature related to Artificial Intelligence and its use in communication. The study results in an understanding of the content that circulates in this digital environment and how this medium sometimes acts to maintain long-established practices and powers.